1998
DOI: 10.1111/j.1469-7793.1998.163bf.x
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal output mapping of human central motor representation on different spatial scales

Abstract: Non‐invasive mapping by focal transcranial magnetic stimulation (TMS) is frequently used to investigate cortical motor function in the intact and injured human brain. We examined how TMS‐derived maps relate to the underlying cortical anatomy and to cortical maps generated by functional imaging studies. The centres of gravity (COGs) of TMS maps of the first dorsal intersosseus muscle (FDI) were integrated into 3‐D magnetic resonance imaging (MRI) data sets in eleven subjects. In seven of these subjects the TMS‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
93
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 43 publications
8
93
0
Order By: Relevance
“…Projected coil trajectories for the primary motor cortex showed greater variability. This is likely because we made adjustments in coil positioning to target where stimulation resulted in the maximum MEP amplitude; previous studies have reported that this location can vary among individuals (Classen et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Projected coil trajectories for the primary motor cortex showed greater variability. This is likely because we made adjustments in coil positioning to target where stimulation resulted in the maximum MEP amplitude; previous studies have reported that this location can vary among individuals (Classen et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…110% MT intensity was then used to map both muscles' representations. Maps were derived by acquiring 5 MEPs of the target muscle with the stimulator at 110% of MT at locations on the 1 ϫ 1 cm grid constructed around CZ (24). Mapping proceeded in an anterior-posterior and medial-lateral direction until at least 4/5 MEPs were absent.…”
Section: Methodsmentioning
confidence: 99%
“…For the targeted muscle, there is usually one small circumscribed area from which the largest MEP responses can be elicited (referred to as a ''hot spot'') with smaller responses being evoked from adjacent positions (24). In accordance with the medial and lateral M1 activation demonstrated by fMRI, the motor maps of the target foot muscle in Füsslers S2 and S3 were not only extensive but also showed two distinct areas, or hot spots, from which maximal MEP responses were elicited-one medial and one lateral ( Fig.…”
Section: Two M1 Foot Representations With Direct Output To Spinal Motormentioning
confidence: 99%
See 1 more Smart Citation
“…The TM training model leverages three physiological principles: (1) improved reflexive gait patterning attributed to altered afferent proprioceptive input, (2) augmented locomotor entrainment with task-repetition that animal and human studies show is crucial for motor learning [39][40], and (3) progression of metabolic demands of the training stimulus by increasing velocity, grade, training session duration, and total program length. The latter principle of progression raises fundamental questions regarding which exercise formulas can optimally improve functional and metabolic health outcomes.…”
Section: Task-oriented Training: Combining Locomotor Learning With Aementioning
confidence: 99%